CONTENT ANALYSIS AND SOCIAL NETWORK ANALYSIS: A TWO-PHASE METHODOLOGY IN OBTAINING FUNDAMENTAL CONCEPTS OF COOPETITION - Suzanna Lamria Siregar; Giovanni Battista Dagnino; Francesco Garraffo (Jurnal Ilmiah Ekonomi Bisnis, 2009)
This study introduces a two-phase methodology in obtaining fundamental concepts from literature. Content analysis performed in the first phase leads to the most frequent concepts scholars used in scrutinizing a theme. Social networkanalysis in the second phase results a network of the relationships between concepts and examines the importance of every concept in the network. To elucidate the advantage of the methodology, the study applies the methodology onCoopetition – to cooperate and compete simultaneously – literature. Ten most frequent concepts occur in the coopetition literature are: Competition, Cooperation, Coopetition, Knowledge, Market, Network, Relationships, Resources, Strategy and Value. Under the social network analysis terms, the importance of every concept in the network is denoted in degree, closeness and betweenness centrality measures. Ranging from the most important concepts to the least are Relationships, Strategy, Resources, Competition, Cooperation, Coopetition, Market, Network, Value and Knowledge.Keywords: content analysis, social network analysis, coopetition